The Effectiveness of Religious Affairs Office Role of Deli Serdang Regency in Implementing Sakinah Family Guidance Services - Ardiansyah, Ardiansyah; Marpaung, Watni; Siagian, Abdul Hakim (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
Research thesis is The Effectiveness of the Role of Religious Office of the District Deli Serdang in Implementing Sakinah Family Guidance Service (Study of Anlysis of High Divorce Rates in Deli Serdang Regency. Type of this research is qualitativ, with normative and empirical approach. The primary source in this research is the regulation of the Minister of Religion of the Republic Indonesia Number 34 of 2016, article 3. The results of observations, documentation and the result of interview with several informants Sub-Distric Role Religious Office and community in Deli Serdang Regency. Research result: The effectiveness of the role the sub-district Religious Affairs Office in Deli Serdang Regency in implementing sakinah family guidance services. In general, the sakinah family guidance services carried otu by the Religious Affairs Office in Deli Serdang Regency have been carried out well and effectively in accordance with the amant of the Regulation of the Mininster of Religion of Republic Indonesia Number 34 of 2016, article 3 regarding guidance of the sakinah family, maximum support is needed form the partisipant. Government to implement regulations related to the guidance of sakinah families, increase the period of implementation of activities, provision of facilities and sufficient funds, as well as adequate staff.